THE PHONETIC FEATURES OF THE SCOTTISH IMMIGRANT: MORPHOPHONEMIC PERSPECTIVE - ICUS PRIHATINI, PUTRI (Language Horizon: Journal of Language Studies, 2015)
Abstrak Studi ini fokus pada segi fonetik pada imigran asal Scotland. Imigran asal Scotland dipilih sebagai partisipan karena pengucapan imigran ini berbeda dengan pengucapan standar bahasa Inggris pada umumnya dan pada dasarnya Scotland sendiri memiliki bahasa inggris standar Scotland. Study ini mengidentifikasi aksen dan menemukan faktor-faktor yang mempengaruhi aksen dari imigran. Metode yang digunakan pada studi ini adalah metode deskriptif kualitatif Munhall (2007) dan menerapkan prosedur dari Miles and Huberman’s, meliputi pengurangan data, penyajian data, dan kesimpulan. Studi ini menggunakan pendekatan teori dari Aitken’s vowel or The Scottish Vowel Length Rule (SVLR) and Stuart-Smith (1993) untuk Scottish Standard English, and Harrington, Cox and Evans (1997) untuk teori Australian Standard English. Holmes (1992) digunakan untuk menemukan factor mengapa aksen imigran Scotland berbeda dengan aksen Inggris pada umumnya. Studi ini menunjukkan bahwa dalam komunikasi sehari-harinya imigran Scotland menggunakan dua aksen, yaitu Scotland aksen dan Australia Aksen namun dia lebih sering menggukan aksen Scotland sebagai aksen asalnya. Disisi lain, studi ini juga menemukan beberapa faktor yang mempengaruhi aksen dari imigran. Pertama, pola penggunaan bahasa yang berkaitan dengan sosial ekonomi faktor, misalnya dimana ia bekerja. Kedua, faktor demografis yang ditunjukkan dari lingkup jangkauan imigran. Kata kunci : fonologi, aksen, imigran, artikulasi fonetik, Scotland. Abstract This study focuses on the phonetic features of the Scottish Immigrant. It is chosen because Scottish immigrant pronunciation is different from Standard English and basically Scotland has Standard English. This study identify the accent that is used by Scottish Immigrant and find out the factors that contributes the accent of the immigrant. The design of this study is descriptive qualitative method by Munhall (2007) and Miles and Huberman’s procedure including data reduction, data display and conclusion. This study is conducted by using Aitken’s vowel or The Scottish Vowel Length Rule (SVLR) and Stuart-Smith (1993) for Scottish Standard English, and Harrington, Cox and Evans (1997) for Australian Standard English. The theory of Holmes (1992) is used to find out the factors why the accent of Scottish immigrant is different from Standard English. This study shows that the immigrant used two accents, Scottish English and Australian English, in his daily communication but Scottish accent as his ethnic accent is most frequently used. In the other side, the study finds out the factors that contribute the Scottish immigrant’s accent different from Standard English. First, the pattern of language use which is contribute by socio economic factor, such as where the jobs are. The second factor is demographic factor which is shown by the network of the immigrant. Key words : phonology, immigrant, accent, articulatory phonetic, Scottish.